Developing Online Learning Based Lesson Plan for Teaching Speaking in 21st Century - Akmaliyah, Afiyah; Hidayat, Hendi (STIT Buntet Pesantren Cirebon, 2022)
This study was intended to develop online learning-based lesson plans for teaching speaking in the 21st century. This research using a qualitative approach, purposed to be a research and development (R&D) method with the ADDIE model, involved several steps, analysis phase, design phase, and development phase, including expert judgments. This research uses literature review as the primary data resource and teachers as the secondary data resources—the techniques of this research use literature review and interviews. The participants were English teachers. From the findings of the need analysis, what teachers need in developing a lesson plan consists of presenting all components of a lesson plan, providing both language skills and content, presenting various learning styles, relevant examples, intrinsic motivation, students' potential optimization, considering the difficulty level of material, development level of students, facilitating multicultural and comfortable classroom interaction, Encouraging students to be proactive, creative, and critical learners in online learning, presenting an assessment of learning outcomes in various aspects and techniques. The last is providing constructive feedback on all assignments and assessments. Based on expert judgments, revisions were made to the learning objectives, teaching activities, and assessment sections. This product is applicable to use.